FORMULASI DAN EVALUASI FISIK SEDIAAN LIPTINT EKSTRAK DAUN JATI (Tectona Grandis Linn.f) - Christiandari, Hanita; Hernawan, Jarot Yogi; Laila, Wahyu Kumil (Jurnal Riset Kefarmasian Indonesia, 2025)
Teak leaves (Tectona grandis L.f.) are known to contain anthocyanin compounds that function as natural dyes and have antioxidant activity. This study aims to formulate and evaluate lip tint preparations using teak leaf extract as a natural dye. Method: extraction using a maceration method with 70% ethanol solvent acidified with citric acid, resulting in the characteristic red color of anthocyanins. Three lip tint formulas were created with varying extract concentrations (40%, 50%, and 60%) and evaluated through organoleptic, homogeneity, pH, spreadability, and hedonic tests. The results showed that all formulas were homogeneous, thick in texture, with colors varying from pink to deep red. The pH of the formulas was within the safe range for lips (4.6–5.5), and the spreadability met the standards for comfortable use. Formula 3 with a 60% extract concentration showed the best results in terms of color, pH, and panelist preference. Conclusion: teak leaf extract has the potential to be used to develop safe, high-quality, and environmentally friendly herbal lip tints.